Arsenite stress variably stimulates pro‐oxidant enzymes, anatomical deformities, photosynthetic pigment reduction, and antioxidants in arsenic‐tolerant and sensitive rice seedlings. (30th April 2015) - Tripathi, Preeti; Singh, Rana Pratap; Sharma, Yogesh Kumar; Tripathi, Rudra Deo
Abstract Contamination of arsenic (As) in rice (Oryza sativa L.) paddies and subsequent uptake by rice plants is a serious concern, because rice is a staple crop for millions of people. Identification of As toxicity and detoxification mechanisms in paddy rice cultivars would help to reduce As‐associated risk. Arsenic tolerance and susceptibility mechanisms were investigated in 2 differential As‐accumulating rice genotypes, Triguna and IET‐4786, selected from initial screening of 52 rice cultivars as an As‐tolerant and an As‐sensitive cultivar, respectively, on the basis of root and shoot length during various arsenite (AsIII) exposures (0–50 μM). Indicators of oxidative stress, such as pro‐oxidant enzymes (reduced nicotinamide adenine dinucleotide phosphate [NADPH] oxidase and ascorbate oxidase) and nitric oxide, were more numerous in the sensitive cultivar than in the tolerant cultivar. Arsenic‐induced anatomical deformities were frequent in the sensitive cultivar, showing more distorted and flaccid root cells than the tolerant cultivar. Chlorophyll and carotenoid synthesis were inhibited in both cultivars, although the decline was more prominent in the sensitive cultivar at higher doses of As. Furthermore, the tolerant cultivar tolerated As stress by producing more antioxidants, such as proline, sustaining the ratio of ascorbate, dehydroascorbate, and glutathione peroxidase (GPX) activity as well as As detoxifying enzymes arsenate reductase, whereas these respective metabolic activities declined in sensitive cultivar, resulting in greater susceptibility to As toxicity. Environ Toxicol Chem 2015;34:1562–1571. © 2015 SETAC